2022
DOI: 10.3233/cbm-203119
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 (MMP-9) promoter -1562C/T functional polymorphism is associated with an increased risk to develop micropapillary thyroid carcinoma

Abstract: BACKGROUND: Matrix metalloproteinase-9 (MMP-9) is an important mediator of tumor initiation and progression. The MMP-9 promoter -1562C/T functional polymorphism increases gene expression and was identified as a susceptibility factor for various cancers. OBJECTIVE: To evaluate the influence of the MMP-9 promoter genotype on the risk of developing papillary thyroid cancer (PTC) and to correlate cancer patient genotype with the clinical and pathological phenotype. METHODS: We evaluated 236 patients with nodular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Serum MMP-9 levels measured using an immunometric assay were evaluated in subjects with PTC in a case-control study that concluded that although serum MMP-9 is not helpful in the diagnosis of PTC, a high pre-surgical level might be a prognostic factor that could dictate the treatment aggressiveness [ 60 ]. In a recent study that investigated the role of MMP-9 promoter −1562C/T functional SNP in the risk of developing PTC, the T allele was found significantly more frequently in subjects with PTC (17.5% vs. 10.1%, p = 0.019) [ 61 ]. PTC had an increased risk of developing in subjects with the CT or CT + TT genotype.…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Serum MMP-9 levels measured using an immunometric assay were evaluated in subjects with PTC in a case-control study that concluded that although serum MMP-9 is not helpful in the diagnosis of PTC, a high pre-surgical level might be a prognostic factor that could dictate the treatment aggressiveness [ 60 ]. In a recent study that investigated the role of MMP-9 promoter −1562C/T functional SNP in the risk of developing PTC, the T allele was found significantly more frequently in subjects with PTC (17.5% vs. 10.1%, p = 0.019) [ 61 ]. PTC had an increased risk of developing in subjects with the CT or CT + TT genotype.…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 99%
“…PTC had an increased risk of developing in subjects with the CT or CT + TT genotype. Although MMP-9 promoter SNP seems to increase the susceptibility of developing PTC, it was not associated with tumor histological subtype, invasion, or tumor stage [ 61 ]. Nevertheless, despite these promising results that strongly suggest a role for MMP-9 SNPs in thyroid carcinogenesis, future research is still needed on larger populations.…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 99%